Optimalisasi Pengendalian Mutu Guna Mengurangi Jumlah Kerusakan Produk Pada IKM Tempe 21 A Yosodadi Metro Timur - Selamet Fuadi; Suryadi; Surya Aji Dewanda (Universitas Muhammadiyah Metro, 2024)
The research problem formulation is what are the factors that cause the amount of productdamage and how to optimize quality control to reduce the amount of product damage in IKMTempe 21A Yosodadi Metro Timur. how to optimize quality control to reduce the amount ofproduct damage in IKM Tempe 21A Yosodadi Metro Timur. The type of research isqualitative research, the data collection technique uses observation, and interviews. Thisstudy focuses on the implementation of Quality Control (quality control) in IKM Tempe 21AYosodadi Metro Timur. Based on the results of research and discussion, it can be concludedthat the factors that cause the amount of damage to tempe products in Mr. Khairunas' TempeIKM consist of lack or excess of yeast, duration of fermentation, changing room temperatureconditions, washing soybeans that are not clean, damaged machines. , and the quality ofsoybeans and how to reduce the amount of product damage, namely ensuring the size of theyeast with the appropriate amount of soybeans so that there is no shortage or excess,ensuring cleanliness in soybean washing, ensuring the fermentation process is good enoughwithout overlapping tempeh, and repairing the machine and seeing the quality of soybeans.become raw materials.